Aplikasi K-means cluster untuk pengelompokan unit kerja yang beresiko Covid-19 pada industri layanan kesehatan - Dias Irawati Sukma; Hasiholan Manurung (Operations Excellence: Journal of Applied Industrial Engineering, 2020)
The pandemic of COVID-19 infection is an epidemic that is of major concern now more than the dengue epidemic that continues to occur today. The focus of risk, especially on medical and non-medical personnel working specifically in health services, is very high because it deals directly with co-19 patients or other patients who are likely to suffer but have not been detected with other illnesses. Related to this, the human resources working in the health service are affected as well as the health conditions and habits that are carried out daily that affect the level of risk that might occur. Covid-19 positive patients who must be hospitalized usually have acute respiratory distress which can be fatal. Identification of patients with Covid-19 infection is usually obtained after laboratory examinations which in less than half are based on congenital (comorbid) diseases such as diabetes, hypertension and those related to the heart and blood vessels.